Construction of anatomical models as a didactive tool for Neurophysiology classes at undergraduate level (Research, Society and Development, 2022)
A wide range of studies has shown the need for professors to review some of their pedagogical practices, primarily when the content being taught is complex and abstract. With this in mind, the current research aims to develop a new and more effective approach to teaching neural physiology. The chosen methodology was a practical activity in which 1st-year students of Nursing and Pharmacy had to assemble a model of nerve cells. The students were given general guidelines but were free to decide on the materials to build the model. Our results showed that students produced high-quality and accurate models, including details of morphophysiological structures of neurons. Thus, the construction of models is an interesting didactic tool in lessons about complex and abstract topics such as neurophysiology. The use of models motivated students and increased their interest in the content covered by the lecturer.